Research on Characteristic Advantage and Winning Mechanism of Mosaic Warfare - Lu Yingqi, Fan Chengli, Liu Lianfei, Guo Zhengming (Editorial Office of Aero Weaponry, 2021)
Mosaic warfare is a new subversive military concept put forward by the US military, which is facing the future war, aiming at strategic opponents and relying on the cutting-edge technology. Once it forms actual combat capability, it will generate a series of nonlinear combat effects and form asymmetrical advantage over the major combat opponents. Based on the analysis of the background of mosaic warfare concept, the characteristic advantage of mosaic warfare are analyzed and condensed from the aspects of the improvement of force design efficiency, the optimization of command and control process, and the innovation of operation mode. The winning mechanism of mosaic warfare is analyzed in the aspects of multi-layer circular nesting of OODA, strong anti-attack ability, high reconstruction efficiency and intelligent fast destruction of the opponent’s OODA ring.